Sosialisasi Pemeliharaan Kesehatan Lambung dan Pola Makan Sehat di Panti LKSA Santa Anna Bojonegoro - Miftahul Jannah; Murtini Murtini (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2026)
Gastric health problems such as gastritis and Gastroesophageal Reflux Disease (GERD) remain common, particularly among children and adolescents, due to irregular eating patterns, excessive consumption of spicy and acidic foods, and a lack of understanding of healthy lifestyles and proper nutrition. The partner of this Community Service Program (PKM) was LKSA Santa Anna Orphanage in Bojonegoro, where limited knowledge regarding gastric health, differences between gastritis and GERD, and preventive efforts was identified among the residents. This PKM activity aimed to increase partners’ knowledge and awareness of gastric health maintenance through the application of healthy eating patterns, balanced nutrition, and appropriate lifestyle practices. The program included educational sessions, interactive discussions, and simple demonstrations to enhance participants’ understanding and engagement. Previous studies indicate that health education and regular eating habits are effective in preventing gastric disorders; therefore, this socialization activity is expected to encourage positive and sustainable healthy behavioral changes, improve daily dietary habits, and support long-term gastric health and overall well-being.